Gestión municipal y su relación con el desempeño laboral en la Municipalidad Provincial de Maynas, periodo 2023 - Quio Lopez, Auria Isabel (2025)
The present research aimed to determine the relationship between Municipal Management and Job Performance in the Provincial Municipality of Maynas, 2023, the research approach was quantitative, non-experimental design and transactional design type and correlational study scope, included as a study population 566 workers of the Provincial Municipality of Maynas, leaving a sample of 229 participants, it was considered to use the survey technique as a data collection instrument and a Likert scale questionnaire as an instrument, it was concluded that there is a positive and moderate relationship between Municipal Management and Job Performance (Spearman's Rho = 0.490, p = 0.000). This indicates that an improvement in municipal management is associated with better employee performance, although there are other factors that also influence job performance; Furthermore, transparency in accountability has a positive and moderate relationship with job performance (Rho = 0.459, p = 0.000), thus having a positive impact. Furthermore, more transparent administration can generate employee trust, fostering their commitment and efficiency in their duties. Efficiency in financial administration also has a positive and moderate relationship with job performance (Rho = 0.485, p = 0.000). Proper resource management and efficient financial management are strongly related to employee productivity and satisfaction.